Selenomethionine Supplementation Mitigates Liver Dysfunction, Oxidative Injury and Apoptosis through Enhancing Antioxidant Capacity and Inhibiting JNK MAPK Pathway in Piglets Fed Deoxynivalenol-Contaminated Diets - Haopeng Zhong; Zhouyin Huang; Lin Li; Xingping Chen; Tiande Zou; Jun Chen; Jinming You (MDPI AG, 2024)
This research evaluated the impacts of selenomethionine (Se-Met) on hepatic functions, oxidative stress, mitochondrial function, and apoptosis of piglets fed deoxynivalenol (DON)-contaminated diets. Twenty-four piglets were allocated four dietary treatments (n = 6) in a 28-day feeding trial. The four treatments included the control group, which received 0.3 mg/kg of Se (as Se-Met) without DON treatment, and the DON treatment groups received 0, 0.3, or 0.5 mg/kg Se as Se-Met. A dietary addition of 0.5 mg/kg Se improved liver pathology and reduced serum aspartate aminotransferase and lactate dehydrogenase levels in piglets fed DON-contaminated diets. Furthermore, 0.5 mg/kg Se mitigated the oxidative stress and apoptosis of piglets fed DON-contaminated diets, as indicated by the decreased reactive oxygen species level, and the down-regulated mRNA levels of NRF-1, Bax, and CASP9 in the liver. Importantly, 0.5 mg/kg Se enhanced the hepatic antioxidant capacity, as evidenced by increased hepatic total antioxidant capacity, catalase, glutathione peroxidase, and total superoxide dismutase activities, as well as the up-regulated mRNA levels of Nrf2, Gclm, NQO1, SOD1, and GPX1 in the liver. Moreover, 0.5 mg/kg Se down-regulated the p-JNK protein level in the liver of piglets fed DON-contaminated diets. Collectively, Se-Met supplementation mitigated liver dysfunction, oxidative injury, and apoptosis through enhancing antioxidant capacity and inhibiting the JNK MAPK pathway in piglets fed DON-contaminated diets.